SWIMMING AGAINST THE CURRENT: ASTHMA AND UPPER AIRWAY DISORDERS IN COMPETITIVE SWIMMERS - Weronika Sepioło; Ilona Boniakowska; Ilona Kamińska; Maria Wydra; Jakub Przerwa; Joanna Wąsik; Izabela Stachowicz; Eliza Gawron; Kacper Gryboś; Julia Samborska; Anna Łysik (International Journal of Innovative Technologies in Social Science, 2025)
Purpose of the research: This review aims to assess the frequency of asthma and upper airway disorders in competitive swimmers, as well as identify potential environmental and training factors that contribute to the development of these conditions.Materials and methods: The review of research literature was conducted through databases such as PubMed, Google Scholar, and Scopus, including studies from 2007 to 2025.Results: Competitive swimmers have been shown to have a significantly higher incidence of exercise-induced asthma and chronic upper respiratory tract syndromes than in the general population. Particularly frequently observed cough, nasal congestion, wheezing, and bronchial hyperresponsiveness. There was also a correlation between the length of exposure to the swimming pool environment and the severity of the symptoms.Conclusions: The environment of indoor swimming pools, especially exposure to chlorination byproducts, may contribute to the development of asthma and chronic upper respiratory tract diseases in swimmers. There is a need for further research and implementation of preventive measures, such as improving swimming pool ventilation and monitoring the health of athletes.